Intermediate microeconomic theory tools and step-by-step examples - Espinola-Arredondo, Ana; Muñoz-Garcia, Felix (MIT Press, 2020)
An intermediate microeconomics textbook geared for students in need of a more hands-on, less rigorous treatment of the material--Provided by publisher.